Green synthesis of Iron oxide and Iron dioxide nanoparticles using Euphorbia tirucalli: characterization and antiproliferative evaluation against three breast cancer cell lines - Ipeleng Kopano Rosinah Kgosiemang; Ayodeji Mathias Adegoke; Samson Sitheni Mashele; Mamello Patience Sekhoacha (Journal of Experimental Nanoscience)
Researchers have become increasingly interested in nanoparticles made from plants because of their stability and large surface area. In the current study, iron oxide and iron dioxide nanoparticles were synthesized using aerial parts of the E. tirucalli as a reducing agent. The nanoparticles were analyzed using various techniques, including Ultraviolet-visible spectroscopy, Fourier Transform Infrared spectroscopy, X-ray diffractometer, X-ray photoelectron spectroscopy, X-ray energy dispersive spectroscopy, Scanning electron Microscopy, and Transmission Electron Microscopy. The nanoparticles were then investigated for their antiproliferative effect against MCF-7, SK-BR-3, MDA-MB231, and Vero cell lines. The results confirmed the formation of FeO and FeO2 nanoparticles by color change and a UV absorbance peak between 220–390 nm. EDS analysis showed traces of Fe and O, while TEM confirmed the nanoparticle size of 100 nm. FTIR showed a peak at 514 nm. The FeO-RT NPs demonstrated over 80% antiproliferative activity against the MCF-7 cell line at a concentration of 10 μg/mL. while doxorubicin, FeO-RT NPs, and DCM extract showed similar activity against the MDA-MB231 cell line at 10 and 1 g/mL concentrations. However, Vero and SK-BR-3 cell lines showed decreased antiproliferative activity. This study highlights the environmentally friendly use and safe application of iron oxide NPs in cancer therapy.